A process for the preparation of a sodium alpha-olefinsulfonate two-phase foam

CN122937672APending Publication Date: 2026-10-20NORTH CHINA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611181064.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]综上分析,引入第三相组分的方法虽然有效,但不可避免地引入新的化学物质或固相组分,改变泡沫作为气-液两相体系的基本属性;并且第三相组分的引入容易导致起泡性能显著下降,难以实现起泡性与稳定性的协同提升

Benefits of technology

本发明通过对水进行磁化处理,然后将磁化水与α-烯烃磺酸钠混合制备AOS发泡基液,并采用通气法制得AOS两相泡沫。本发明通过对作为发泡基液连续相的水进行物理磁化处理以改变水分子簇结构与氢键网络,从而赋予水相活化特性,进而影响α-烯烃磺酸钠分子在气-液界面的吸附行为与排列状态;而且,经磁化水配制的发泡基液在通气时能够形成更为细密、均匀且液膜强度更高的泡沫结构,在保持气-液两相纯净体系的前提下,协同提升AOS两相泡沫的起泡能力与稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the technical field of two-phase foam materials, specifically relating to a method for preparing sodium α-olefin sulfonate two-phase foam. The invention involves magnetizing water, then mixing it with sodium α-olefin sulfonate to prepare a foaming base liquid, and finally producing AOS two-phase foam using a gas-permeation method. The magnetization parameters are: magnetic field strength of 10 mT to 225 mT, magnetization time of 1 min to 60 min, and water flow rate of 0.03 m / s to 0.12 m / s. By controlling the magnetization parameters, this invention physically modifies the aqueous phase without introducing a third phase, synergistically improving the foaming properties, stability, and size uniformity of the AOS two-phase foam. Compared to the unmagnetized group, the AOS two-phase foam prepared by this invention exhibits a foaming ratio increase of over 20% and a half-life extension of over 30%. The preparation method of this invention is simple and highly controllable, and the resulting foam has wide applications in mineral flotation, fire extinguishing, and oil extraction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of two-phase foam material preparation technology, specifically relating to a method for preparing sodium α-olefin sulfonate two-phase foam. Background Technology

[0002] Two-phase foams have wide applications in mineral flotation, oil extraction, fire fighting, and dust removal. Their performance directly depends on the foam's foaming ability and stability. Two-phase foams typically consist of a gaseous phase (such as air or nitrogen) and a liquid phase containing surfactants. The surfactant, acting as a foaming agent, is the key component determining the foam's performance. Sodium α-olefin sulfonate (AOS) is a commonly used anionic surfactant for preparing two-phase foams due to its strong foaming properties and good biodegradability.

[0003] To improve the overall performance of two-phase foam, existing technologies typically employ the approach of optimizing surfactant formulations by compounding different types of surfactants to utilize their synergistic effects. However, optimizing surfactant formulations increases the complexity and cost of the formulation; moreover, compounded systems are prone to weakening the foaming ability of the system due to phenomena such as competitive adsorption or aggregation between molecules.

[0004] In addition, some researchers have constructed composite systems by introducing a third phase component, such as adding water-soluble polymers (e.g., xanthan gum, polyacrylamide) to increase liquid phase viscosity and slow down liquid film drainage. While adding polymers can effectively improve foam stability, it usually leads to a significant decrease in foaming performance. Alternatively, micro / nano solid particles (e.g., nano-silica, bentonite, or calcium carbonate) can be added to adsorb at the gas-liquid interface and form a mechanical barrier, thereby preparing stable three-phase foams. Although micro / nano solid particles can significantly enhance foam stability by forming steric hindrance at the gas-liquid interface through adsorption, they inhibit foaming performance.

[0005] In summary, while the method of introducing a third phase component is effective, it inevitably introduces new chemical substances or solid components, changing the fundamental properties of foam as a gas-liquid two-phase system. Furthermore, the introduction of a third phase component can easily lead to a significant decrease in foaming performance, making it difficult to achieve a synergistic improvement in foaming properties and stability. Summary of the Invention

[0006] To address the shortcomings of existing optimization strategies for AOS two-phase foam, which weaken the foaming ability of the system and make it difficult to achieve a synergistic improvement in foaming properties and stability, this invention provides a method for preparing AOS two-phase foam that does not require the addition of a third phase substance and produces a pure system.

[0007] This invention magnetizes water, then mixes the magnetized water with an AOS surfactant to prepare a foaming base solution, and uses an aeration method to produce AOS two-phase foam. Magnetizing the water alters the water molecule cluster structure and hydrogen bond network, thereby endowing the aqueous phase with activation properties, which in turn affects the adsorption behavior and arrangement of AOS molecules at the gas-liquid interface. Furthermore, the foaming base solution prepared with magnetized water can form a finer, more uniform foam structure with higher liquid film strength during aeration, synergistically improving the foaming ability and stability of the foam while maintaining the purity of the gas-liquid two-phase system.

[0008] This invention provides a green and controllable new physical regulation approach for the preparation of high-performance two-phase foams by systematically controlling magnetization parameters to physically modify the aqueous phase without introducing a third phase. Furthermore, compared to unmagnetized AOS two-phase foams, the AOS two-phase foam prepared by this invention exhibits significant improvements in both foaming properties and stability.

[0009] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: This invention provides a method for preparing sodium α-olefin sulfonate two-phase foam, comprising the following steps: Water is magnetized under the following conditions: magnetic field strength of 10 mT to 225 mT, magnetization time of 1 min to 60 min, and water flow rate of 0.03 m / s to 0.12 m / s to obtain magnetized water. The magnetized water is then mixed with sodium α-olefin sulfonate to obtain AOS foaming base liquid, with a sodium α-olefin sulfonate mass concentration of 0.05% to 2%. A protective gas is then introduced into the AOS foaming base liquid to obtain AOS two-phase foam.

[0010] Preferably, the mass concentration of sodium α-olefin sulfonate in the AOS foaming base solution is 0.1%. The concentration of sodium α-olefin sulfonate is a fundamental factor affecting foam performance: when the mass concentration of sodium α-olefin sulfonate is too low, the number of surfactant molecules adsorbed at the gas-liquid interface is insufficient, making it difficult to form a stable foam structure; when the mass concentration of sodium α-olefin sulfonate is too high, surfactant molecules form a large number of micelles in the solution, which is not conducive to their rapid adsorption at the new interface, and also increases the raw material cost.

[0011] Preferably, the magnetization conditions are: magnetic field strength of 30mT to 125mT, magnetization time of 10min to 30min, and water flow rate of 0.06m / s to 0.09m / s. Controlling the magnetization conditions (magnetic field strength and magnetization time) and the flow rate of deionized water alters the hydrogen bond network and cluster structure of water molecules, thereby regulating the surface tension, critical micelle concentration, and microscale distribution of the foam, ultimately affecting the foaming performance. A moderate magnetic field strength effectively reduces surface tension and refines bubbles; an excessively strong magnetic field disrupts the dynamic equilibrium of hydrogen bonds, weakening foam stability. Too short a magnetization time results in insufficient magnetization, while too long a time leads to the reformation of hydrogen bonds, causing a decrease in the magnetization effect. The water flow rate determines the magnetization efficiency by controlling the residence time of water molecules in the magnetic field and the degree of Lorentz force interaction; excessively fast or slow water flow rates are detrimental to achieving the desired hydrogen bond breaking effect. Overall, a reasonable combination of magnetization parameters can significantly improve the foaming ratio and half-life of foam, make the bubble size smaller and more uniformly distributed, and reduce the concentration of surfactant used, thereby achieving efficient and economical foam performance optimization.

[0012] Preferably, the water is deionized water. Deionized water removes calcium, which is commonly found in natural water bodies. 2+ Mg 2+ The removal of mineral ions and suspended impurities prevents these ions from being polarized by the magnetic field during magnetization, thus avoiding additional interference and ensuring that the magnetization effect is entirely attributable to changes in the structure of water molecule clusters and hydrogen bond networks.

[0013] Preferably, the conditions for introducing the protective gas are: the flow rate of the protective gas is 0.8 L / min to 1.2 L / min, the pressure is 0.005 MPa to 0.01 MPa, and the time is 8 min to 12 min.

[0014] Preferably, the protective gas is nitrogen.

[0015] Compared with the prior art, the present invention has the following technical effects: This invention prepares an AOS foaming base solution by magnetizing water and then mixing the magnetized water with sodium α-olefin sulfonate, and then uses an aeration method to produce AOS two-phase foam. This invention alters the water molecule cluster structure and hydrogen bond network by physically magnetizing the water, which serves as the continuous phase of the foaming base solution, thereby endowing the aqueous phase with activation properties. This, in turn, affects the adsorption behavior and arrangement of sodium α-olefin sulfonate molecules at the gas-liquid interface. Furthermore, the foaming base solution prepared with magnetized water can form a finer, more uniform foam structure with higher liquid film strength during aeration, synergistically improving the foaming ability and stability of the AOS two-phase foam while maintaining the purity of the gas-liquid two-phase system.

[0016] This invention achieves a significant improvement in the performance of AOS two-phase foam without adding a third-phase substance. This technical approach completely preserves the pure gas-liquid two-phase system of the foam, fundamentally avoiding the complex formulation, increased costs, and potential environmental impacts caused by the introduction of a third-phase substance, and simplifying the production process.

[0017] The AOS two-phase foam prepared by this invention has a foaming ratio that is more than 20% higher than that of the unmagnetized control group and a half-life that is more than 30% longer. Attached Figure Description

[0018] Figure 1 This is a comparison chart of the expansion ratio and half-life of AOS two-phase foam under different magnetic field strengths.

[0019] Figure 2 A comparison of the expansion ratio and half-life of AOS two-phase foams at different magnetization times.

[0020] Figure 3 A comparison of the expansion ratio and half-life of AOS two-phase foam at different flow rates.

[0021] Figure 4 The images show the microstructure of AOS two-phase foam under different magnetic field strengths. Specifically, a is the microstructure of AOS two-phase foam in the unmagnetized control group of Comparative Example 1; b is the microstructure of AOS two-phase foam under a magnetic field strength of 30 mT in Example 1; and c is the microstructure of AOS two-phase foam under a magnetic field strength of 125 mT in Example 1.

[0022] Figure 5 Frequency distribution of particle size distribution in AOS two-phase foam under different magnetic field strengths. Detailed Implementation

[0023] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings.

[0024] Unless otherwise specified, all reagents used in this invention are commercially available, and all methods used are conventional techniques in the art.

[0025] The raw materials used in the following examples are all commercially available conventional products without special limitations: industrial-grade sodium α-olefin sulfonate (AOS) surfactant with an activity content ≥90%; deionized water was prepared in the laboratory; industrial-grade high-purity nitrogen with a purity ≥99.99%.

[0026] All experimental setups used were standard laboratory equipment: magnetic field treatment device (adjustable magnetic field strength 0mT~300mT), constant flow pump (flow rate adjustment range 0.000166m / s~0.12m / s), aeration foaming device (including nitrogen cylinder, gas flow meter, pressure gauge, and foaming container with bubble stones at the bottom), stereo microscope, and electronic balance (accuracy 0.001g).

[0027] This invention screens AOS concentrations: AOS foaming base solutions with mass concentrations of 0.05%, 0.1%, 0.3%, 0.5%, 1%, and 2% were prepared using deionized water and transferred to an aerated foaming apparatus. A nitrogen flow rate of 1 L / min and a system pressure of 0.007 MPa were set, and aeration was carried out for 10 min to prepare AOS two-phase foam. The expansion ratio was tested according to GB15308-2006 standard, and the half-life of the AOS two-phase foam (the time required for the foam volume to decrease by half) was tested using the static observation method. Considering the expansion ratio, half-life, and the economic efficiency of surfactant dosage, 0.1% was determined as the optimal concentration of AOS for subsequent magnetization treatment.

[0028] Example 1 This embodiment is used to investigate the effect of magnetic field strength on the properties of AOS two-phase foam.

[0029] A method for preparing AOS two-phase foam includes the following steps: Magnetization treatment: Deionized water is magnetized by a magnetic field device, and the flow rate of deionized water through the magnetization device is controlled by a constant flow pump. The parameters of magnetization treatment and the flow rate of deionized water through the magnetization device are shown in Table 1, and different groups of magnetized water are obtained.

[0030] Each group of magnetized water was mixed with AOS to obtain an AOS foaming base solution with a mass concentration of 0.1%. The AOS foaming base solution was transferred to an aerated foaming device, and the nitrogen flow rate was set to 1 L / min and the system pressure to 0.007 MPa. The nitrogen source was turned on for aeration. During the aeration process, the foaming container was kept still to avoid external disturbance to the foam formation. After continuous aeration for 10 min, the foam was collected in a plastic container, the nitrogen source was turned off, and the preparation of AOS two-phase foam was completed.

[0031] Table 1. Parameters and flow rates of magnetization treatment and deionized water Magnetic field strength / mT 0 10 30 50 85 125 225 Magnetization time / min 15 15 15 15 15 15 15 <![CDATA[Flow velocity / m·s -1 > 0.06 0.06 0.06 0.06 0.06 0.06 0.06 Average equivalent diameter / mm 0.84 0.81 0.58 0.67 0.51 0.74 0.72 Number of bubbles / each 35 35 58 69 114 50 62 The expansion ratio and half-life of AOS two-phase foam were tested, and the results showed that the magnetic field strength had a significant impact on both the macroscopic properties and microstructure of the AOS two-phase foam. Figure 1As shown, with the magnetic field strength increasing from 0 mT to 30 mT, the foaming ratio increased from 186 to 257 (an increase of 38.2%), and the half-life increased from 5.62 h to 28.5 h (an increase of 407.1%). When the magnetic field strength is too high (≥125 mT), the foaming ability is suppressed, and only the stability improvement can be partially maintained. Simultaneously, combined with... Figure 4 The microstructure of foam and Figure 5 Particle size distribution frequency analysis showed that the unmagnetized control group had a wider foam particle size distribution with an average diameter of 0.84 mm, and contained many large bubbles with diameters greater than 1.2 mm. These bubbles had thin walls and were prone to aggregation and rupture. The 30 mT magnetized group exhibited a highly concentrated foam particle size distribution within the small size range, consistent with the macroscopic properties of foaming ratio and half-life. The proportion of small bubbles (0–0.6 mm) increased from 31.43% in the unmagnetized control group to 51.72%, effectively refining the foam and enhancing liquid film stability. The 125 mT magnetized group still showed better foaming ratio and half-life than the unmagnetized control group, indicating that higher magnetic field strength can still improve performance by enhancing liquid film stability.

[0032] The above results indicate a threshold effect in regulating foam performance: too low a magnetic field strength results in insignificant magnetization; too high a magnetic field strength leads to excessive water structuring, which in turn inhibits the orderly arrangement of AOS molecules at the interface, resulting in decreased foaming performance. Under the conditions of this embodiment, magnetic field strength in the range of 10–225 mT has a positive impact on foam performance, with better overall performance in the range of 30 mT. Therefore, a magnetization intensity of 30 mT was selected for investigation in the following embodiments.

[0033] Example 2 This embodiment is used to investigate the effect of magnetization time on the properties of AOS two-phase foam.

[0034] A method for preparing AOS two-phase foam includes the following steps: Magnetization treatment: Deionized water is magnetized by a magnetic field device, and the flow rate of deionized water through the magnetization device is controlled by a constant flow pump. The parameters of magnetization treatment and the flow rate of deionized water through the magnetization device are shown in Table 2, and different groups of magnetized water are obtained.

[0035] Each group of magnetized water was mixed with AOS to obtain an AOS foaming base solution with a mass concentration of 0.1%. The AOS foaming base solution was transferred to an aerated foaming device, and the nitrogen flow rate was set to 1 L / min and the system pressure to 0.007 MPa. The nitrogen source was turned on for aeration. During the aeration process, the foaming container was kept still to avoid external disturbance to the foam formation. After continuous aeration for 10 min, the foam was collected in a plastic container, the nitrogen source was turned off, and the preparation of AOS two-phase foam was completed.

[0036] Table 2. Parameters and conditions for magnetization treatment Magnetic field strength / mT 30 30 30 30 30 30 30 Magnetization time / min 0 1 5 10 15 30 60 <![CDATA[Magnetization flow velocity / m·s -1 > 0.06 0.06 0.06 0.06 0.06 0.06 0.06 The expansion ratio and half-life of AOS two-phase foam were tested, such as... Figure 2 As shown, compared to the unmagnetized control group, the foaming ratio was significantly improved after magnetization treatment. Specifically, the foaming ratio reached a peak of 545 after 5 minutes of magnetization, an increase of 193.0% compared to the unmagnetized control group. The foaming ratio rapidly increased within 1 to 5 minutes of magnetization, then significantly decreased after 5 minutes, stabilizing between 10 and 15 minutes. It slightly increased again between 30 and 60 minutes, but did not exceed the peak value at 5 minutes. The half-life of the magnetized group was significantly higher than that of the unmagnetized group, reaching a peak of 28.50 h after 15 minutes of magnetization, an increase of 407.1% compared to the unmagnetized control group. The half-life fluctuated between 15.23 and 18.67 h within 1 to 10 minutes of magnetization, reaching a peak at 15 minutes, and gradually decreasing after 15 minutes. Both the foaming ratio and half-life were significantly improved within the magnetization time range of 10 to 30 minutes. Considering the balance between foaming capacity and stability, under the test conditions set in this embodiment, the foam expansion ratio and half-life of the foam exhibited good overall performance when the magnetization time was 15 minutes. The following embodiments selected a magnetization time of 15 minutes for further investigation.

[0037] Example 3 A method for preparing AOS two-phase foam includes the following steps: Magnetization treatment: Deionized water is magnetized using a magnetic field device; the flow rate of deionized water through the magnetization device is controlled by a constant flow pump; the parameters of magnetization treatment and the flow rate of deionized water through the magnetization device are shown in Table 3, and different groups of magnetized water are obtained.

[0038] Each group of magnetized water was mixed with AOS to obtain an AOS foaming base solution with a mass concentration of 0.1%. The AOS foaming base solution was transferred to an aerated foaming device, and the nitrogen flow rate was set to 1 L / min and the system pressure to 0.007 MPa. The nitrogen source was turned on for aeration. During the aeration process, the foaming container was kept still to avoid external disturbance to the foam formation. After continuous aeration for 10 min, the foam was collected in a plastic container, the nitrogen source was turned off, and the preparation of AOS two-phase foam was completed.

[0039] Table 3. Parameters and conditions for magnetization treatment Magnetic field strength / mT 30 30 30 30 30 30 Magnetization time / min 15 15 15 15 15 15 <![CDATA[Magnetization flow velocity / m·s -1 > 0.03 0.04 0.05 0.06 0.09 0.12 like Figure 3As shown, the foaming ratios of the magnetized group were significantly higher than those of the unmagnetized control group. Specifically, the foaming ratio reached a peak of 450 at a magnetized flow rate of 0.09 m / s, an increase of 141.9% compared to the unmagnetized group. Within the range of 0.03–0.06 m / s, the foaming ratio fluctuated between 257 and 329, increasing sharply at 0.09 m / s and then decreasing again at 0.12 m / s. Simultaneously, the half-life of the magnetized group was significantly longer than that of the unmagnetized group, reaching a peak of 28.50 h at a flow rate of 0.06 m / s, an increase of 407.1% compared to the unmagnetized control group. Within the range of 0.03–0.05 m / s, the half-life ranged between 21.45 and 22.58 h, peaking at 0.06 m / s and gradually decreasing after exceeding 0.06 m / s. Considering the balance between foaming capacity and stability, 0.06 m / s is the optimal magnetization flow rate parameter. At this point, the foaming ratio is 257 (an increase of 38.2%), and the half-life is the highest among all groups, resulting in the best overall foam performance.

[0040] Comparative Example 1 A method for preparing AOS two-phase foam includes the following steps: Deionized water and AOS were mixed to obtain an AOS foaming base solution with a mass concentration of 0.1%. The AOS foaming base solution was transferred to an aerated foaming device, and the nitrogen flow rate was set to 1 L / min and the system pressure to 0.007 MPa. The nitrogen source was turned on for aeration. During the aeration process, the foaming container was kept still to avoid external disturbance to the foam formation. After continuous aeration for 10 min, the foam was collected in a plastic container, the nitrogen source was turned off, and the preparation of AOS two-phase foam was completed.

[0041] Comparative Example 2 A method for preparing AOS two-phase foam includes the following steps: Deionized water was magnetized using a magnetic field device. The magnetization conditions were controlled as follows: magnetic field strength 5 mT, magnetization time 15 min, and deionized water flow rate 0.06 m / s, resulting in magnetized water. The magnetized water was then mixed with AOS to obtain an AOS foaming base solution with a mass concentration of 0.1%.

[0042] Transfer the AOS foaming base liquid to the aerated foaming device, set the nitrogen flow rate to 1L / min and the system pressure to 0.007MPa, and turn on the nitrogen source for aeration. During the aeration process, keep the foaming container stationary to avoid external disturbance to the foam formation. After aeration for 10 minutes, collect the foam with a plastic container, turn off the nitrogen source, and complete the preparation of AOS two-phase foam.

[0043] Comparative Example 3 A method for preparing AOS two-phase foam includes the following steps: Deionized water was magnetized using a magnetic field device. The magnetization conditions were controlled as follows: magnetic field strength 300 mT, magnetization time 15 min, and deionized water flow rate 0.06 m / s, resulting in magnetized water. The magnetized water was then mixed with AOS to obtain an AOS foaming base solution with a mass concentration of 0.1%.

[0044] Transfer the foaming base liquid to the aerated foaming device, set the nitrogen flow rate to 1L / min and the system pressure to 0.007MPa, and turn on the nitrogen source for aeration; keep the foaming container stationary during the aeration process to avoid external disturbance to the foam formation; after aeration for 10 minutes, collect the foam with a plastic container, turn off the nitrogen source, and complete the preparation of AOS two-phase foam.

[0045] Comparative Example 4 A method for preparing AOS two-phase foam includes the following steps: Deionized water was mixed with AOS to obtain an AOS foaming base solution with a mass concentration of 0.01%.

[0046] Transfer the AOS foaming base liquid to the aerated foaming device, set the nitrogen flow rate to 1L / min and the system pressure to 0.007MPa, and turn on the nitrogen source for aeration. During the aeration process, keep the foaming container stationary to avoid external disturbance to the foam formation. After aeration for 10 minutes, collect the foam with a plastic container, turn off the nitrogen source, and complete the preparation of AOS two-phase foam.

[0047] Comparative Example 5 A method for preparing AOS two-phase foam includes the following steps: Deionized water was mixed with AOS to obtain an AOS foaming base solution with a mass concentration of 0.3%.

[0048] Transfer the AOS foaming base liquid to the aerated foaming device, set the nitrogen flow rate to 1L / min and the system pressure to 0.007MPa, and turn on the nitrogen source for aeration. During the aeration process, keep the foaming container stationary to avoid external disturbance to the foam formation. After aeration for 10 minutes, collect the foam with a plastic container, turn off the nitrogen source, and complete the preparation of AOS two-phase foam.

[0049] Comparative Example 6 A method for preparing AOS two-phase foam includes the following steps: Deionized water, AOS, and xanthan gum were mixed to obtain a foaming base solution with a mass concentration of 0.1% AOS and 0.05% xanthan gum.

[0050] Transfer the AOS foaming base liquid to the aerated foaming device, set the nitrogen flow rate to 1L / min and the system pressure to 0.007MPa, and turn on the nitrogen source for aeration. During the aeration process, keep the foaming container stationary to avoid external disturbance to the foam formation. After aeration for 10 minutes, collect the foam with a plastic container, turn off the nitrogen source, and complete the preparation of AOS two-phase foam.

[0051] Table 4. Expansion ratio and half-life of AOS two-phase foams from Comparative Examples 1 to 6 Foaming ratio 186 436.3 380.00 841.43 535.45 163.61 Half-life / h 5.62 17.83 20.28 9.43 23.43 43.25 As shown in Table 4, the AOS two-phase foams of Comparative Examples 1 to 6 exhibited an increase in large air bubbles and voids during preparation; the AOS two-phase foam of Comparative Example 4 showed a breakage in the middle of the foam column during preparation. This indicates that the stability of AOS two-phase foams is poor when the water is not magnetized, or when the concentration of the AOS foaming base solution is not appropriate and the magnetization parameters are not reasonable. Comparative Examples 1-6 were set up as controls in four dimensions: blank baseline, magnetization intensity, reagent concentration, and chemical foam stabilization. Each group had obvious performance shortcomings: Comparative Example 1, as a blank baseline, had low foaming capacity and foam stability, short half-life, and insufficient long-term foam stabilization capacity; Comparative Example 2, with its low-intensity magnetization, had insufficient regulatory effect, limited performance improvement, and the half-life remained at a low level; Comparative Example 3, with its high-intensity magnetization, thickened the AOS molecular hydration layer and hindered interfacial adsorption, resulting in a significant decline in foaming capacity and a narrowing of overall gain; Comparative Example 4, with its low-concentration system, had a high foaming ratio, but the half-life was much shorter than that of the magnetized modified group, limiting its liquid carrying capacity and long-term foam stabilization capacity; Comparative Example 5, with its high-concentration system, relied on increased reagent dosage for efficiency improvement, increasing raw material costs, diminishing marginal efficiency, and hindering the reduction of the environmental burden of chemical reagents; Comparative Example 6, with its xanthan gum chemical foam stabilization, significantly extended the half-life, but significantly weakened foaming capacity and significantly increased system viscosity, which easily led to increased resistance in the delivery pipeline and limited spreading and penetration in micropores. In summary, medium-intensity magnetization modification can simultaneously improve foaming and foam stabilization performance without increasing the amount of reagent or introducing additional components, resulting in a more prominent overall advantage.

[0052] In summary, this invention physically magnetizes deionized water, which serves as the continuous phase of the foaming liquid, and controls reasonable magnetization parameters to alter the water molecule cluster structure and hydrogen bond network, thereby endowing the aqueous phase with activation properties and influencing the adsorption behavior and arrangement of AOS molecules at the gas-liquid interface. Furthermore, the foaming base liquid prepared with magnetized water can form a finer, more uniform foam structure with higher liquid film strength when aeration is performed, thus synergistically improving the foaming ability and stability of the foam while maintaining the purity of the gas-liquid two-phase system.

[0053] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range, as well as any value between the two endpoints, can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described in this invention to avoid redundancy. Although preferred embodiments of this invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments, and all such changes and modifications fall within the scope of this invention.

[0054] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. If these modifications and variations fall within the scope of equivalents of this invention, then this invention also intends to include these modifications and variations.

Claims

1. A method for preparing sodium α-olefin sulfonate two-phase foam, characterized in that, Includes the following steps: The water was magnetized under the following conditions: magnetic field strength of 10 mT to 225 mT, magnetization time of 1 min to 60 min, and water flow rate of 0.03 m / s to 0.12 m / s to obtain magnetized water. Magnetized water was mixed with sodium α-olefin sulfonate to obtain AOS foaming base solution, wherein the mass concentration of sodium α-olefin sulfonate was 0.05% to 2%. A protective gas is introduced into the AOS foaming base liquid to obtain AOS two-phase foam.

2. The method for preparing sodium α-olefin sulfonate two-phase foam according to claim 1, characterized in that, In the AOS foaming base solution, the mass concentration of sodium α-olefin sulfonate is 0.1%.

3. The method for preparing sodium α-olefin sulfonate two-phase foam according to claim 1, characterized in that, The magnetization conditions are: magnetic field strength of 30mT to 125mT and magnetization time of 10min to 30min.

4. The method for preparing sodium α-olefin sulfonate two-phase foam according to claim 1, characterized in that, The water flow velocity is 0.06 m / s to 0.09 m / s.

5. The method for preparing sodium α-olefin sulfonate two-phase foam according to claim 1, characterized in that, The water is deionized.

6. The method for preparing sodium α-olefin sulfonate two-phase foam according to claim 1, characterized in that, The protective gas is nitrogen.

7. The method for preparing sodium α-olefin sulfonate two-phase foam according to claim 6, characterized in that, The conditions for introducing protective gas are: the flow rate of protective gas is 0.8 L / min to 1.2 L / min, the pressure is 0.005 MPa to 0.01 MPa, and the time is 8 min to 12 min.